Saskatchewan : North sheet - Canada. Department of Mines and Technical Surveys (Department of Mines and Technical Surveys Canada, 1963)
This is a general map of Saskatchewan in 1963 showing highways and roads (paved and graveled), gas and oil mines, First Nations reserves, national and provincial parks, railways, cities and towns. It consists of 2 parts - North sheet and South sheet (see also Saskatchewan : South sheet). "M.C.R. 45 (Sheet 2)" Scale 1:760,320, or 12 miles to 1 inch. Relief shown by spot heights. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Shows highways and roads (paved and graveled); gas and oil mines; First Nations reserves; national and provincial parks; railways, cities and towns.